Nematodes of freshwater fish from the Primorsk region - Belous, E. V. (Parasitic worms of domestic and wild animals: Papers on Helminthology presented to Prof. AA Sobolev on the 40th anniversary of his scientific and teaching activity, 1965)
From a survey of helminths of freshwater fish in the Primorsk region, USSR, Rhabdochona coronacauda n.sp. and R. longispicula n.sp. from Leuciscus brandti, Erythrocuher spp. and other fish, Spinitectus petrawi [also spelt petrowi] n.sp. from Pseudobagrus fulvidraco, Cucullanus mugili n.sp. from Mugil soiuy, Philometra biglobocerca n.sp. from M. soiuy, P. trilabiata n.sp. from Carassius auratus gibelio and P. schikhobalowi n.sp. from Cyprinus carpi are described and figured.